2021
DOI: 10.18502/jri.v22i2.5792
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Post warming Culture Period Between Thawing and Transfer of Cryopreserved Embryos on Reproductive Outcomes After In Vitro Fertilization (IVF): A Systematic Review and Meta-analysis

Abstract: Background: The purpose of this study was to evaluate the effect of post warming culture period between thawing and transfer of cryopreserved embryos on reproductive outcomes after in vitro fertilization (IVF). Methods: An extensive literature search was performed using PubMed, EmBase, and the Cochrane library from January 2000 to August 2019. A systematic review and meta–analysis of clinical trials was performed in this manuscript. The trials represented patients with embryo transfers of at least one pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Our data also clearly showed that the live birth rate after transfer of thawed blastocysts was not affected by the post‐warming culture time. These findings are similar to those of a meta‐analysis including five studies that investigated the effect of post‐warming culture on reproductive outcomes 23 . The meta‐analysis found no differences in clinical pregnancy, implantation, and live birth rates between culture times of 2 h vs. overnight 23 .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our data also clearly showed that the live birth rate after transfer of thawed blastocysts was not affected by the post‐warming culture time. These findings are similar to those of a meta‐analysis including five studies that investigated the effect of post‐warming culture on reproductive outcomes 23 . The meta‐analysis found no differences in clinical pregnancy, implantation, and live birth rates between culture times of 2 h vs. overnight 23 .…”
Section: Discussionsupporting
confidence: 83%
“…These findings are similar to those of a meta-analysis including five studies that investigated the effect of post-warming culture on reproductive outcomes. 23 The meta-analysis found no differences in clinical pregnancy, implantation, and live birth rates between culture times of 2 h vs. overnight. 23 Haas et al (2018) investigated the delay of blastocyst transfer until 20-22 h after warming, and reported that the ongoing pregnancy rate was the same after transfer of goodquality blastocysts, whether they developed further during the culture or not.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, it was comparable between cycles that had and had not resulted in a live birth. Moreover, the time interval between embryo warming and transfer was found not to affect reproductive outcome [22]. Third, there was a significant heterogeneity in the characteristics of the studied cycles, including the use of PGT-A in some, but not all, cycles.…”
Section: Discussionmentioning
confidence: 91%
“…There is no final consensus on the optimum thaw culture time required. [ 5 ] This study was done to find the best day of thawing, culture and day of transfer of embryos by comparing their clinical pregnancies to improve our clinical outcome.…”
Section: Introductionmentioning
confidence: 99%